Suzuki Cross‐Coupling Reaction with Genetically Encoded Fluorosulfates for Fluorogenic Protein Labeling. Issue 68 (27th October 2020) - Zhao, Qian; Guo, Guoying; Zhu, Weiwei; Zhu, Liping; Da, Yifan; Han, Ying; Xu, Hongjiao; Wu, Shuohan; Cheng, Yaping; Zhou, Yani; Cai, Xiaoqing; Jiang, Xianxing
Abstract: A palladium‐catalyzed cross‐coupling reaction with aryl halide functionalities has recently emerged as a valuable tool for protein modification. Herein, a new fluorogenic modification methodology for proteins, with genetically encoded fluorosulfate‐l ‐tyrosine, which exhibits high efficiency and biocompatibility in bacterial cells as well as in aqueous medium, is described. Furthermore, the cross‐coupling of 4‐cyanophenylboronic acid on green fluorescent protein was shown to possess a unique fluorogenic property, which could open up the possibility of a responsive "off/on" switch with great potential to enable spectroscopic imaging of proteins with minimal background noise. Taken together, a convenient and efficient catalytic system has been developed that may provide broad utilities in protein visualization and live‐cell imaging. Abstract : Compatible modifications : A protein fluorogenic modification methodology based on genetically encoded fluorosulfate‐l ‐tyrosine, which exhibits high efficiency and biocompatibility in bacterial cells and in aqueous medium, is reported. This protein modification strategy can be further used for protein fluorogenic labeling to enable in vitro and in vivo imaging of proteins with minimal background noise.